Designing sustainable kidney care through product innovation and life cycle assessment of dialysis pathways - Larkin, James (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2026)
This thesis investigates how society approaches the sustainability of kidney healthcare, using the example of dialysis pathways to map the environmental, social, practical and ethical complexities that define modern medicine. Kidney care, particularly haemodialysis (HD) and peritoneal dialysis (PD), is among the most resource intensive fields in medicine, requiring large volumes of energy, water and singleuse plastics and generating substantial hazardous waste. With the number of patients needing life sustaining kidney replacement therapy (KRT) rising sharply due to global demographic and epidemiological trends, the environmental footprint of dialysis is growing at a rate that challenges not only health systems but the broader goals of climate neutrality, resource stewardship and social justice. The thesis is situated within the KitNewCare project, a European wide collaborative effort supported by Horizon funding to decarbonise kidney treatment through innovation in clinical practice, product development and policy advocacy. The projects multi-disciplinary scope brings together designers, clinicians, engineers, data scientists and procurement officials to develop practical methods and tools that shape everyday decision making. Among the outputs of this thesis are educational toolkits and guidelines for clinicians, operational dashboards for environmental monitoring and methodological improvement in LCA analysis of healthcare systems at multiple scales. The work has been published in leading peer reviewed journals, influencing national and European strategy, procurement guidelines and greener pilot initiatives in hospitals. Through a thorough and original programme of life cycle assessment (LCA), this thesis quantifies the impacts of dialysis modalities across multiple categories, including climate change, energy use, toxicity and resource depletion. The thesis also identifies the root cause of high environmental impacts within clinical procurement, manufacturing processes and service organisation, such as product specifications, costs, supplier location and waste classification rules. By mapping treatment pathways in detail, including material flows, energy consumption, transport, packaging and waste management, the work provides a comprehensive picture of the environmental burden of dialysis. It presents the first process based LCAs of PD and HD pathways at product, treatment and system level in a European setting and integrates social life cycle assessment (S-LCA) to examine labour risk exposure in dialysis supply chains. The result is a robust evidence base that helps empower clinicians, hospital administrators and policymakers to identify specific products, practices and system designs that disproportionately contribute to emissions and resource consumption. In investigating PD, the research demonstrates the significant influence of single use plastics, transport logistics and hazardous waste disposal on the total environmental burden. Through process based LCAs, the thesis reveals that consumables such as dialysate bags, tubing and packaging account for the majority of emissions and waste. Annual plastic consumption for a single PD patient can exceed one tonne, most of which is incinerated, producing toxins such as dioxins, heavy metals and greenhouse gases (GHG). These results raise practical questions about how PD equipment is specified and purchased. They suggest that procurement teams and manufacturers need to reconsider material choices, product configurations and packaging. The work looks at alternative pathways, such as on-site dialysate mixing, localised production and closed loop materials management, demonstrating the potential for substantial footprint reductions without compromising treatment success. In HD, the thesis quantifies the high energy and water demands of hospital based treatments. An individual HD session requires hundreds of litres of water, much of which is wasted in the production of ultra-pure dialysate. The process is further burdened by the reliance on energy-intensive machines and complex, multi component disposable kits. The environmental impacts of transport and packaging are critical hotspots, especially for acid and bicarbonate concentrates. The research compares system innovations, such as centralised acid preparation and shows that replacing single use liquid bags with bulk powder or central preparation substantially reduces emissions and waste while streamlining logistics and improving operational resilience. The quantitative output of this thesis is complemented and deepened by qualitative analysis. Semi structured interviews and thematic analysis engage over two dozen European stakeholders, including clinicians, hospital managers, procurement experts and policy advisors. Participants discuss tensions between infection control requirements, workload and staffing, procurement rules and waste regulations and their wish to reduce environmental impacts. The interviews uncover motivators and barriers, from the perception of sustainability as a secondary concern in patient care to the need for clear information and leadership at multiple levels. Survey data supplement these insights, identifying gaps in awareness, training and engagement among healthcare students and clinicians and helping shape recommendations for future professional education and system change. A unique contribution of this thesis is the integration of social life cycle assessment (S-LCA), which examines the ethical aspects of procurement and clinical systems. The research shows the presence of medium to high risk labour exposure embedded in the supply chains for dialysis products, many of which are manufactured or disposed of under conditions that challenge global standards for equity and environmental justice. By looking at environmental and social impacts together, the thesis advocates a triple bottom line approach to sustainability that foregrounds not only carbon and pollution reduction but also the fair distribution of risks and benefits. The research highlights the complexity of turning environmental data into practice. Recognising the operational challenges of hospitals, the thesis proposes implementation pathways for sustainable procurement and waste treatment, explaining how environmental performance metrics can be embedded in tender evaluations, clinical dashboards and policy frameworks such as the NHS Net Zero Supplier Roadmap and the European Green Deal. The thesis makes the underlying life cycle assumptions and datasets as transparent as possible. It recommends that manufacturers and health systems share comparable product level data so that environmental performance can be routinely included in procurement and service planning. The participatory approach to data collection and tool development, involving clinicians, engineers and suppliers, ensures that findings are not only technically sound but institutionally feasible. This thesis integrates design, environmental quantification, social ethics, professional training and policy strategy into a unified model, providing a platform from which science, clinical practice and public health policy can continue to evolve. By linking environmental and social hotspots to specific products, processes and procurement decisions, this thesis offers a guide for greener kidney care that does not compromise patient safety or access. It provides recommendations for product redesign, waste reclassification, centralised fluid delivery and integration of LCA into procurement and education, supporting health system decarbonisation strategies.
APPROVED